Analisis Pengelolaan Air Berdasarkan Konsep Green Building Pada Greenship - Margareta Ajeng Prabawati; Henita Rahmayanti; Doddy Rochadi (Menara: Jurnal Teknik Sipil, 2018)
The purpose of this research is to analyze the water management system at Raden Dewi Sartika Building and provide recommendation in water management in accordance with the existing conditions of the building as an effort of water utilization based on greenship GBCI criteria. Data collecting was conducted by observing the condition of existing water management system in buildings and water. Water demand analysis based on number of building occupants calculated based on the national standard. The analyze of water management on this building using greenship rating tools as the standar. The results of water management research on the building Raden Dewi Sartika get the amount of water requirement of 148,128 liters /day with the amount of waste grey water that can be reprocessed to meet the needs of flushing on the building by 31.8% of the amount of water a day. With greenship, Raden Dewi Sartika Building has fulfilled the benchmarks in the category of recycled water and potable water. But at the potable water category, its processing system was inactive and sub meter water for control water usage was not plugged in. Overall the water management on the building already reach 25% based on the assestment by using greenship